Queue Systems Evaluation of Fast food Industrial - Rorim Panday; Ayuna Suci Hartati; Dovina Navanti (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2019)
The queuing system can influent customer satisfaction and always interesting to analyze. The queuing at HokBen use a Single Channel Multi-Phase system, 1 service to offer and prepare order menus and 1 cashier. The study was conducted at the Hokben Ujung Menteng Store in East Jakarta, for one week, at 4 sessions during rush hour. After the data obtained, a Single Channel Multi-Phase queue parameter was calculated, namely: the average arrival per unit time, the average service unity of time, the level of server usage, the number of customers in the queue, the number of customers in the system, the waiting time in the queue, the waiting time in the system, and customer probabilities in the system. The result showed that the customer's arrival pattern meets the Poison distribution and the service pattern meets the Normal distribution, but the service time still greater than the standard service time, and of course not satisfy to customers, because they waited a bit longer. After a multi-channel multiphase simulation, which used 2 service lines, the service time smaller than the standard service time, and service more efficient. This research becomes useful for Hokben management specifically, and also for the fast-food industry in general.